Nutritional Contents of Catfish (Pangasius Sp.) Jambal Roti Products Sidenreng Rappang Regency, South Sulawesi - Amir, Nursinah; Syahrul; Hafifah, Nur; N. Papalan, Alriomesta; Arianti, Annisa; Aidil Akbar, Farid; Wahyuramadan (Hasanuddin University, 2024)
Catfish (Pangasius sp.) is a popular type of freshwater fish that has the potential to be cultivated in Indonesia. So far, the use of catfish, especially those from Sidenreng Lake, Sidenreng Rappang Regency, South Sulawesi, has not been optimal. Catfish is only used as a fresh commodity without processing and preservation activities. One of the well-known preserved products is jambal roti. Jambal roti is a product of salt fermentation. This research aims to analyze the nutrition contents of jambal roti catfish, Sidenreng Rappang Regency, South Sulawesi. The research method used was experimental with a Completely Randomized Research Design. The treatment was long fermentation (24, 36, and 48 hours) at a salt concentration of 30%. The parameters observed were water content, salt content, protein, fat, and amino acids. The research results showed that the treatment given significantly affected water content, salt content, protein, fat, and amino acids. The best treatment is a fermentation period of 36 hours.